Perancangan Website UMKM Barak Ummy Menggunakan Aplikasi Visual Studio Code Untuk Pengembangan Pemasaran Dan Promosi jasa - Riska Mutmainah; Audy dwi Guna kencana putri; Arvan Adha (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
The influence of current technology can change the marketing strategies of all business people. Where the right business strategy in this advanced era will advance the business. This encourages business people to adopt innovative marketing strategies, especially through online media. This article documents the design and implementation of an e- Commerce website for MSMEs offering gifts and hampers, focusing on the case study "Barak Ummy". In this project, we chose the Blogger platform as the main development tool for creating a website. Several stages of website creation are data collection, system analysis, website design using the blogger platform. This project aims to increase product exposure, expand market reach, and improve the marketing and product promotion process for MSMEs. The result of implementing this project is a website. This project is expected to be beneficial for MSMEs by increasing the number of customers.